Decarboxylase activity involved in methyl ketone production by Staphylococcus carnosus 833, a strain used in sausage fermentation - Fadda, Silvina G. (2002)
Staphylococcus carnosus strain 833, inoculated into sausage, increased the levels of methyl ketones which contributed to the cured aroma. These ketones were predicted to arise from incomplete β-oxidation followed by a decarboxylation. To check this hypothesis, we measured the β-decarboxylase activity in resting cells of S. carnosus grown in complex or in synthetic medium, using as substrate a β-ketoacid, which can be an intermediate of the β-oxidation pathway. This activity was present throughout the growth period. The enzyme appeared to be constitutive because no induction was observed. High aeration, a pH of 5 and the presence of nitrate promoted the production of methyl ketones.